2009
DOI: 10.1517/17425250903012360
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and protein–protein interactions in PXR-mediated CYP3A repression

Abstract: Background The expression of drug-metabolizing enzymes cytochrome P450 (CYPs) is controlled by pregnane X receptor (PXR), and therefore understanding how PXR modulates CYP expression is important to minimize adverse drug interactions, one type of preventable adverse drug reaction. Objective We review the mechanisms of PXR-mediated repression of CYP expression Methods We discuss the clinical implications of CYP repression and the role of signal cross-talks, including protein-protein interactions and phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 108 publications
1
60
0
Order By: Relevance
“…Hepatic CYP gene expression is affected by various signaling mechanisms, including reversible phosphorylation (Sidhu and Omiecinski, 1995;Marc et al, 2000;Pondugula et al, 2009a), and PXR-mediated CYP gene expression is modulated by both ligand binding and signaling crosstalk. We determined whether the phosphatase PP2C␤l affects hPXR transcriptional activity in HepG2 cells by measuring the activity of the PXR-regulated CYP3A4-luc reporter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic CYP gene expression is affected by various signaling mechanisms, including reversible phosphorylation (Sidhu and Omiecinski, 1995;Marc et al, 2000;Pondugula et al, 2009a), and PXR-mediated CYP gene expression is modulated by both ligand binding and signaling crosstalk. We determined whether the phosphatase PP2C␤l affects hPXR transcriptional activity in HepG2 cells by measuring the activity of the PXR-regulated CYP3A4-luc reporter.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated a role for phosphorylation-dependent signaling events in regulating PXR-mediated CYP gene expression (Pondugula et al, 2009a). Kinases such as protein kinase A (Ding and Staudinger, 2005a;Lichti-Kaiser et al, 2009), protein kinase C (Ding and Staudinger, 2005b), cyclin-dependent kinase (CDK)2 (Lin et al, 2008), and p70 ribosomal S6 kinase (Pondugula et al, 2009b) phosphorylate PXR and regulate PXR-mediated CYP gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pglycoprotein) and ABCG2 (a.k.a. breast cancer esistance protein, BCRP) (Pondugula et al, 2009, Pondugula andMani, 2013). Activation of PXR by xenobiotics leads to chemoresistance, concern in drug development and clinical therapy.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Post-translational regulation of Pregnane X Receptor 3.3.1 Phosphorylation Phosphorylation of PXR is often inhibitory (Pondugula et al 2009b). Treatment of primary rat and human hepatocytes with protein kinase A (PKA) activator leads to the attenuation of Cyp3A1 (Cyp3A1 is the rat ortholog of human CYP3A4) and CYP3A4 mRNA levels, respectively.…”
Section: 3mentioning
confidence: 99%